Bonding strengths of 2-octyl cyanoacrylate, N-butyl-2- cyanoacrylate, and nylon 10-0 - Jocelyn R. Elises, MD; Leo DP Cubillan, MD (Philippine Journal of Ophthalmology)
Objective: To determine the bonding strength of 2-Octyl cyanoacrylate (Dermabond) compared with N-Butyl-2-cyanoacrylate (Histoacryl) and nylon 10-0 (Alcon,) in sealing experimentally induced corneal perforations in cadaver porcine eyes.